FEMINIZATION OF AGRICULTURE AND COPING WITH CLIMATE VARIABILITY IN THE UPPER EAST REGION OF GHANA - Issahaku, A-R.; Edziyie, R.; Campion, B. B. (UDS International Journal of Development, 2023)
The paper investigated the nexus between feminization of agriculture and coping with climate variability in five selected districts of the Upper East Region in Ghana. The districts were selected because there were women farming groups present in those districts. The study employed both quantitative and qualitative methods and data obtained were analysed using descriptive analysis. The result indicated that 25 (14.5%) of women farmers out of 173 would out-migrate because of climate related factors such as increasing temperature and shortening of rainy days. The study further saw that most people migrate because of decrease in food production, infertile land and poverty. For women farmers of the Upper East Region out-migration and planting trees to absorb the harsh effect of the sun are the mitigating efforts mostly adopted. As a result, women farmers resort to animal rearing (4.0%) and food processing (18.5%) to survive the dry season. Their challenge is lack of capital for agricultural inputs and land. It is recommended that families of migrant male farmers should support female farmers with farmlands. The government and benevolent organizations must also give them financial support, climate smart measures and inputs. Key words: Income, Poverty, Land, Climate Smart Measures, Migration, Food Processing